PATCHWORKED MEDIA: MOBILE DEVICES AND CREATIVE PRACTICE IN CAPE TOWN, SOUTH AFRICA - Venter, Marija Anja (AoIR Selected Papers of Internet Research, 2020)
There has been a recurring narrative in research that revolves around mobile technologies and society, particularly in relation to Africa: that these technologies have the potential to reconfigure and revolutionise the development trajectories of entire countries (Donner & Locke, 2019). But if these narratives are to be the case, then, indeed, the role that mobile devices can play in production (in this case of art, media, and design) is going to have to be something that allows people in the global South to earn a living. This paper presents an exploration of the creative practices, with a focus on mobile creative practices, of a cohort of Extended Curriculum Program (ECP) Visual Design students from a university in Cape Town, South Africa (2014). All of these students came from low-income, resource constrained contexts in the townships that surround Cape Town. In questioning whether mobile technologies can help young South African creatives forge careers or attain resources that could help them do so, the role of mobile technologies is complicated. While these devices offer new emerging creative affordances, and in some cases, can offer means to generate income, the material reality is a different story. I conclude by arguing that instead of these devices offering access to a global network, they, at best, provide the means for young creatives, such as those featured in this study, to a forge a media patchwork.